FORECASTING OF NET PROFIT AND THE AREA OF LAND OF PRIVATE ENTERPRISES - Humeniuk, Mariana; SHELENKO, Diana; Balaniuk, Ivan (My University, 2021)
The article is devoted to the forecasting of net profit of private enterprises of Ukraine with application of STELLA program. The STELLA economic modeling program, which combines mathematical differential equations with a developed graphical interface, has been used in the article. In this program a model was created and an attempt was made to forecast the private enterprises of Ukraine by 2030. It has been the possible growth up net profit of private enterprises with a slight reduction and further stabilization of the agricultural land (AREA) at the level of 45000 thousand hectares and enterprises (ENTERPISES) at the level of 3600. The most promising possibilities of applying STELLA program in economic forecasting has been outlined in the article.
Keywords: private enterprises,net profit forecasting.